2012
DOI: 10.7324/japs.2012.2817
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial and antifungal activities of Tabernaemontana heyneana Wall. leaves

Abstract: Medicinal plants are the oldest source of pharmacologically active compounds and provided virtually the only source of medicinally useful compounds for centuries. They contain physiologically active principles that over the years have been exploited in traditional medicine for the treatment of various ailments. The increased likelihood of acute infections and inflammatory conditions in early humans could have set the stage for the natural selection of the use of medicinal herbs high in antimicrobial and anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The antioxidant activity of the raw extract from the aerial parts of T. catharinensis was lower than that observed in root ethanolic extracts of this species (IC 50 = 100  μ g/mL) [32] but higher than that identified in ethanolic extracts of T. heyneana leaves (IC 50 = 537  μ g/mL) [33]. …”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of the raw extract from the aerial parts of T. catharinensis was lower than that observed in root ethanolic extracts of this species (IC 50 = 100  μ g/mL) [32] but higher than that identified in ethanolic extracts of T. heyneana leaves (IC 50 = 537  μ g/mL) [33]. …”
Section: Resultsmentioning
confidence: 99%
“…The highest number of flavonoids were observed for the stem hexane (946.92 ± 6.29 mg QE/g), latex (768.96 ± 5.43 mg QE/g), stem chloroform (693.24 ± 4.12 mg QE/g), and leaf hexane (662.20 ± 1.00 mg QE/g) extracts respectively whereas the lowest amount was observed for the leaf and stem methanol extracts (Table 3). The total flavonoid content of T. ventricosa extracts showed contrasting results compared to studies by Sathishkumar and Baskar [52]. In their study, the total flavonoid content in the fresh leaves of Tabernaemontana heyneana was much lower with a value of 4.4 ± 0.17 mg QE/g [52].…”
Section: Total Flavonoid Contentmentioning
confidence: 60%
“…The total flavonoid content of T. ventricosa extracts showed contrasting results compared to studies by Sathishkumar and Baskar [52]. In their study, the total flavonoid content in the fresh leaves of Tabernaemontana heyneana was much lower with a value of 4.4 ± 0.17 mg QE/g [52]. However, it has been reported that the accumulation of flavonoids is often associated with drought-tolerant plants, such as the Arabidopsis species [53].…”
Section: Total Flavonoid Contentmentioning
confidence: 63%
“…The stem bark, bitter roots, flowers, and latex of fruits are used in folk medicine to treat diseases of skin and toothache and to reduce inflammation [5]. The indole alkaloids and terpenoids isolated from the roots, stem bark, fruits, and leaves possess cytotoxic, anti-implantation, and antioxidant properties [68]. …”
Section: Introductionmentioning
confidence: 99%